Prevalence of multiple chronic conditions and its impact on physical functioning among community elderly in a district of Shenzhen city - Yingjun MU; Shan XU; Hongen CHEN; Shuhong DAI; Ji ZHANG; Yinxing LIU; Fangfang ZENG; Changyi WANG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the prevalence of multiple chronic conditions (MCC) among community-dwelling elderly in a district of Shenzhen city for providing evidence to life quality promotion of the population. MethodsAt 62 community health care centers in Nanshan district of Shenzhen city and with random cluster sampling and a self-designed questionnaire, face-to-face interview and physical examination were conducted among 4 475 physical examinees aged 65 years and above from 2018 through 2019 to collect information relevant to MCC prevalence. The physical function of the elderly was assessed using grip strength tests and Short Physical Performance Battery assessments. Unconditional multivariate logistic regression analysis was performed to explore the relationship between MCC and physical function decline. ResultsAmong the 4 297 participants included in the final analysis, 2 728 (63.49%) were identified as having MCC; of the MCC sufferers, 1043 (38.23%)，793 (29.07%)，and 892 (32.70%) had two, three, and four and more chronic conditions. Physical function decline was assessed for 745 (17.34%) of all the participants, and the number (percentage) of the participants assessed as having decreased gait speed, prolonged sitting up time, and decreased grip strength were 1 761 (40.98%), 1 475 (35.33%), and 1 761 (40.98%), respectively. After adjusting for sex, age, education, marital status, registered residence, smoking, and alcohol drinking, the results of logistic regression analysis showed that the participants with MCC were at significantly increased risk of reduced physical function (odds ratio [OR] = 1.52, 95% confidence interval [95% CI]:1.26 - 1.82), decreased gait speed (OR = 1.83, 95% CI:1.45 - 2.30), and prolonged sitting up time (OR = 1.22, 95% CI:1.06 - 1.39) compared to those without the conditions. ConclusionThe study findings indicate a high prevalence of MCC and the prevalence is associated with increased risks of physical function decline, reduced gait speed, and prolonged sitting up time among the community-dwelling elderly people in Nanshan district of Shenzhen city.